Caregiver mind-mindedness training as an early intervention for social anxiety in children: A protocol for a randomised controlled trial - Hiva Javadian; Mary E. Stewart; Minu Mathews; Andrew James Williams; Daniel Hale (PLoS ONE, 2025)
Background This paper describes a randomised controlled trial (RCT) protocol aimed at investigating the efficacy of caregivers’ Mind-Mindedness training as an early intervention for preschoolers with social anxiety. Mind-mindedness, a caregiver’s ability to recognise and respond to a child as an individual with their own thoughts, feelings, and intentions, is associated with secure attachment and socioemotional skills. While previous studies indicate brief Mind-Mindedness training may increase caregiver mentalisation in high-risk groups, there is a lack of rigorous evidence assessing its impact specifically on child social anxiety symptoms. Building on the well-established link between caregivers’ Mind-Mindedness and positive socioemotional outcomes in children, this study aims to bridge the existing research gap by directly testing the impact of Mind-Mindedness training on social anxiety. Methods This randomised controlled trial aims to recruit 100 caregivers of preschool-aged 4–7-year-old children with social anxiety from the UK and Iran. The caregivers will be randomly assigned to either a mind-mindedness training group (n = 50) or a peer support (control) group(n = 50). The mind-mindedness training will involve three online sessions, each of one hour duration, focused on teaching strategies for using mind-minded comments with their children, across three consecutive weeks. The peer support (control) group will have access to a private online peer-support platform for sharing experiences. Measures of mind-mindedness, child social anxiety, attachment, and theory of mind will be assessed at baseline, post-intervention, and 3-month follow-up using established assessment tools. Discussion The study aims to evaluate the effectiveness of a mind-mindedness parental intervention for social anxiety in children and to uncover the potential mediating roles of attachment and theory of mind in the relationship between mind-mindedness and child anxiety. The cross-cultural design, involving participants from the UK and Iran, will offer valuable information on the cultural aspect of the intervention. The training group is hypothesised to lead to increased mind-mindedness and reduced child social anxiety versus a peer support (control) group. This research can establish evidence for mind-mindedness training as an early intervention approach for childhood social anxiety, with implications for global mental health strategies targeting early caregiver-child relationships. Trial registration Prospectively registered on ClinicalTrials.gov (ID: NCT06657014; registered on 23rd October 2024) and on the Iranian Registry of Clinical Trials (IRCT) Version 1 (ID: 80088; approved on 2nd November 2024). These registrations promote transparency and ensure compliance with international standards for reporting clinical trials.